Optical xor for Error Detection and Coding of QPSK I and Q Components in PPLN Waveguide - Lazzeri, Emma; Malacarne, Antonio; Serafino, Giovanni; Bogoni, Antonella (IEEE photonics technology letters, 2012)
An all-optical scheme based on periodically-poled lithium niobate (PPLN) waveguide for signal processing of the in-phase (I) and quadrature (Q) components of an input quadrature phase shift keying (QPSK) signal is presented. The device is able to work on the I and Q components without any additional demodulation stage, and makes use of cascaded second harmonic and difference frequency generation in the PPLN to obtain the logical operation xor (I, Q). A single continuous wave signal is needed in addition to the input signal to generate the output signal, in which the information is coded in a binary phase shift keying modulation. The logical xor (I, Q) potentially enables data coding, error detection, and encryption of sensitive information in all-optical networks. Bit error rate measurements are provided to evaluate the system performance for a 20-Gb/s differential-QPSK input signal, and tunability of the output wavelength has been attested with almost constant optical signal-to-noise-ratio penalty along the C-band.